2023
DOI: 10.1021/acsanm.3c02962
|View full text |Cite
|
Sign up to set email alerts
|

Dual Crosslinked Antioxidant Mixture of Poly(vinyl alcohol) and Cerium Oxide Nanoparticles as a Bioink for 3D Bioprinting

Nasera Rizwana,
Namrata Maslekar,
Kaushik Chatterjee
et al.

Abstract: Three-dimensional (3D) bioprinting has made it possible to fabricate structures with intricate morphologies and architectures, which is considered difficult to do when using other conventional techniques like electrospinning. Although the 3D printing of thermoplastics has seen a huge boom in the past few years, it has been challenging to translate this technology to cellbased printing. A major limitation in bioprinting is the lack of inks that allow for the printing of 3D structures that meet the biological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…20,169,170 Peptidedendrimer reinforced bioink (HC-PDN) presents enhanced mechanical properties and bioprinting capabilities, offering prospects for intricate tissue fabrication. 171 Rizwana et al 172 used a dual-cross-linked PVA and cerium oxide (CeO 2 ) nanoparticle composite as a bioink for 3D bioprinting, while Chandra et al (2023) 173 demonstrated CeO 2 's cytocompatibility and oxidative stress protection in mouse myoblast cells, enhancing the potential of bioprinted constructs. Each formulation embodies a balance of advantages and limitations, influencing its suitability for specific bioprinting applications.…”
Section: Nanoclay-based Hybrid Bioinkmentioning
confidence: 99%
See 1 more Smart Citation
“…20,169,170 Peptidedendrimer reinforced bioink (HC-PDN) presents enhanced mechanical properties and bioprinting capabilities, offering prospects for intricate tissue fabrication. 171 Rizwana et al 172 used a dual-cross-linked PVA and cerium oxide (CeO 2 ) nanoparticle composite as a bioink for 3D bioprinting, while Chandra et al (2023) 173 demonstrated CeO 2 's cytocompatibility and oxidative stress protection in mouse myoblast cells, enhancing the potential of bioprinted constructs. Each formulation embodies a balance of advantages and limitations, influencing its suitability for specific bioprinting applications.…”
Section: Nanoclay-based Hybrid Bioinkmentioning
confidence: 99%
“…Polyurethane (PU) showcases excellent biocompatibility and mechanical strength, as evidenced by the GO-PU hybrid, offering improved properties for tissue regeneration. ,, Poly vinyl alcohol (PVA) enables versatile bioinks for cartilage bioprinting with good printability and mechanical properties. , Polylactic- co -glycolic acid (PLGA) nanomaterials enhance rheological characteristics and osteogenic differentiation, showcasing potential for bone tissue engineering. ,, Peptide-dendrimer reinforced bioink (HC-PDN) presents enhanced mechanical properties and bioprinting capabilities, offering prospects for intricate tissue fabrication . Rizwana et al used a dual-cross-linked PVA and cerium oxide (CeO 2 ) nanoparticle composite as a bioink for 3D bioprinting, while Chandra et al (2023) demonstrated CeO 2 ’s cytocompatibility and oxidative stress protection in mouse myoblast cells, enhancing the potential of bioprinted constructs. Each formulation embodies a balance of advantages and limitations, influencing its suitability for specific bioprinting applications.…”
Section: Nanomaterials-based Hybrid Bioinksmentioning
confidence: 99%